Pembelajaran Bahasa Inggris Melalui Kegiatan Outbound: Meningkatkan Keterampilan Kerjasama Dan Komunikasi Siswa Di SMK Negeri 2 Binjai Tahun 2022 - Rudi Purwana; Mariana Mariana; Asrul Asrul; Afina Muharani Syaftriani; Ani Rahmadhani Kaban (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2022)
In this study, English language learning through outbound activities aimed to enhance students' cooperation and communication skills at SMK Negeri 2 Binjai in 2022. The research focused on utilizing outbound activities as a method to improve students' English language proficiency by fostering teamwork and effective communication. The objectives included evaluating the effectiveness of outbound activities in enhancing students' cooperation and communication skills, assessing students' perceptions towards English learning through outbound, and identifying the implications of incorporating outbound activities in English language education. Methods involved observation, interviews, and surveys to gather data on students' participation, perceptions, and learning outcomes. Findings indicated a significant improvement in students' cooperation and communication skills after engaging in outbound activities. The study concludes that incorporating outbound activities in English language learning can effectively promote teamwork, communication, and language proficiency among students.